Semiconducting polymer nano-regulators with cascading activation for photodynamic cancer immunotherapy - He, Shasha (2022)
Combination photoimmunotherapy holds promise for tumor suppression; however, smart phototherapeutic agents that only activate their immune pharmaceutical action in tumors have been rarely developed. Herein, we report a semiconducting polymer (SP) nano-regulator (SPNT ) with cascading activation for combinational photodynamic cancer immunotherapy. SPNT comprises an immunoregulator (M-Trp: 1-methyltryptophan) conjugating to the side chain of the SP backbone via an apoptotic biomarker-cleavable linker. Under near-infrared photoirradiation, SPNT produces singlet oxygen to induce immunogenic apoptosis. Concurrently, an apoptotic biomarker is upregulated, which triggers the specific cleavage of M-Trp for indoleamine 2,3-dioxygenase (IDO) activity inhibition, regulatory T cells reduction and cytotoxic T lymphocytes infiltration. SPNT -mediated combination photodynamic immunotherapy thus reprograms the tumor immune microenvironment, resulting in efficient suppression of tumors, and inhibition of lung metastasis.